Restrukturisasi Kredit Sebagai Solusi Bagi Debitur Terdampak Covid-19 - Arham Rays Tuanaya; Sarah Selfina Kuahaty; Marselo Valentino Geovani Pariela (Faculty of Law, Universitas Pattimura, 2023)
Introduction: This credit restructuring can be carried out on loans or financing provided before or after debtors are affected by the spread of the corona virus disease 2019 (COVID-19) including micro, small and medium business debtors.Purposes of the Research: The purpose of this study was to find out how the procedure for implementing credit restructuring during the COVID-19 pandemic and knowing what the legal consequences of implementing credit restructuring were in credit agreements. Methods of the Research: The research method used is the normative legal research method. The problem approach used is the statutory approach, the conceptual approach. The legal materials used are primary legal materials and secondary legal materials. Procedures and Collection of Legal Materials using the method of inventorying laws and regulations and Processing and Analysis of legal materials using data analysis techniques with deductive logic.Results of the Research: Based on the results of the study, it can be concluded that the legal consequences that occur from the implementation of credit restructuring are changes in the agreement between the bank as the creditor and the borrowing customer as the debtor in the rights and obligations of the parties in the credit agreement.